HAV Matrix: Employee Development in PT. X based on Potential Review Assessment - Nadia Shafira Putri; Endah Mastuti (Psikostudia : Jurnal Psikologi, 2025)
The individual assessment potential review was conducted as part of talent management activities to obtain a comprehensive understanding of the individual’s potential and to identify competencies that require improvement. In addition to providing psychological measures to map employee profiles, the organization also considered performance evaluation results. The tool used in this assessment was the HAV Matrix. The subject of this study was an employee of PT. X. This research employed two data collection methods: psychological testing tools and interviews. At the end of the process, counseling sessions were conducted to provide developmental suggestions tailored to the individual’s needs through counseling programs, aiming to enable the individual to perform optimally. The research findings indicated that the subject falls into the "current star" category in the HAV Matrix analysis, which means the subject is classified as a high performer with moderate potential. This finding confirms that the subject is a promising candidate for the position of Purchasing Section Head but requires further development in certain areas. Penelitian asesmen individu potential review dilakukan sebagai bagian dari kegiatan talent management untuk mendapatkan gambaran menyeluruh tentang potensi yang dimiliki oleh individu serta mengidentifikasi kompetensi yang perlu ditingkatkan. Selain menyediakan pengukuran psikologis untuk memetakan profil karyawan, organisasi juga mempertimbangkan hasil evaluasi kinerja. Tools yang digunakan dalam asesmen ini adalah HAV Matriks. Subjek pada penelitian ini adalah 1 orang karyawan PT. X. Penelitian ini menggunakan dua metode pengumpulan data, yaitu alat tes psikologi dan wawancara. Pada akhir kegiatan dilakukan konseling untuk memberikan saran pengembangan yang diperlukan untuk kebutuhan pengembangan SDM melalui program konseling agar individu dapat bekerja dengan optimal. Hasil penelitian menunjukkan bahwa subjek termasuk dalam kategori “current star” dalam analisis HAV matriks, yaitu subjek berada pada rentang high performer dan moderate potential. Hal tersebut membuktikan bahwa subjek termasuk kader potensial untuk menduduki jabatan kasie purchasing namun membutuhkan beberapa pengembangan.